2014
DOI: 10.1073/pnas.1417827111
|View full text |Cite
|
Sign up to set email alerts
|

Context-dependent incremental timing cells in the primate hippocampus

Abstract: We examined timing-related signals in primate hippocampal cells as animals performed an object-place (OP) associative learning task. We found hippocampal cells with firing rates that incrementally increased or decreased across the memory delay interval of the task, which we refer to as incremental timing cells (ITCs). Three distinct categories of ITCs were identified. Agnostic ITCs did not distinguish between different trial types. The remaining two categories of cells signaled time and trial context together:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 45 publications
(67 reference statements)
2
36
0
Order By: Relevance
“…The findings of time cells in rodents appear to generalize to primates. In monkeys, Suzuki and colleagues (Naya & Suzuki, ; Sakon, Naya, Wirth, & Suzuki, ) have shown that hippocampal neurons track elapsed time in memory tasks, even when the information is task‐irrelevant. Similar to Eichenbaum's work in rats, the findings suggest that the hippocampus may track temporal context as a basis for structuring memory representations as an event unfolds over time.…”
Section: Hippocampal Encoding Of Continuous Temporal Intervalsmentioning
confidence: 99%
“…The findings of time cells in rodents appear to generalize to primates. In monkeys, Suzuki and colleagues (Naya & Suzuki, ; Sakon, Naya, Wirth, & Suzuki, ) have shown that hippocampal neurons track elapsed time in memory tasks, even when the information is task‐irrelevant. Similar to Eichenbaum's work in rats, the findings suggest that the hippocampus may track temporal context as a basis for structuring memory representations as an event unfolds over time.…”
Section: Hippocampal Encoding Of Continuous Temporal Intervalsmentioning
confidence: 99%
“…Although most of the work on temporal coding in the hippocampus has been done in rats, Suzuki and colleagues have also demonstrated neural correlates of temporal coding in recordings from the monkey hippocampus. 61,62 In one study, Naya and Suzuki 62 recorded hippocampal activity during a task that required short-term memory for the temporal order of pairs of objects. Hippocampal neurons fired at specific time points during the delay between each object, which they termed an incremental timing signal.…”
Section: (B) Jenkins and Ranganath 64 Used Functional Magnetic Resonamentioning
confidence: 99%
“…If this is the case, one would expect that the timing signal of hippocampal neurons should carry sequence-specific information under conditions that encourage learning of consistent associations. Sakon et al 61 tested this prediction in an analysis of hippocampal activity during a test of memory for object-place associations. They found that a subset of hippocampal neurons signaled temporal intervals that were specific to particular object-place associations.…”
Section: (B) Jenkins and Ranganath 64 Used Functional Magnetic Resonamentioning
confidence: 99%
“…Neurons that respond during the cues differentiate their activity based on the cue identity [3942] or the associated response to the cue [39,4244] indicating that the hippocampus registers non-spatial events as they occur and the neural response is also contingent on the rules of the task. More recently, it has been shown that cue-specific activity can span the delay period before a response, creating a bridge between the events of the task [45,46]. These task-specific responses develop around the time that the animal learns the contingencies of the experimental paradigm [43,47,48], suggesting that the activity of hippocampal neurons may be the direct result of abstracting conditional relationships across task events.…”
Section: The Function Of the Hippocampus Outside The Spatial Domainmentioning
confidence: 99%